COLLABORATION AND INTEGRATION OF BUSINESS PROCESSES IN THE SUPPLY CHAIN: PROPOSITION OF A CONCEPTUAL MODEL - Milnitz, Diego; Luna, Monica Maria Mendes (Seven Editora, 2025)
The growing complexity of supply chains has increased the need to understand how collaboration and business process integration interrelate to generate value and competitiveness. The literature shows significant progress in defining key processes and collaboration constructs, but studies that analyze the influence of these elements in an integrated manner are still scarce. This article aims to propose a conceptual model that explains how collaboration can positively affect the integration of business processes in the supply chain. The research was developed through a systematic literature review, encompassing classic models (GSCF, SCOR, Handfield & Nichols, Srivastava, and Melnyk) and recent contributions on interorganizational collaboration. As a result, eight fundamental business processes were identified (customer relationships, customer service, demand, orders, manufacturing, suppliers, product development, and returns) and four constructs that precede collaboration (internal alignment, partner trust, collaborative culture, and partnership orientation). These elements were organized into a conceptual model supported by five hypotheses that demonstrate how collaboration enhances process integration. The study's main contribution is to offer a robust theoretical framework that can guide future empirical research using quantitative methods (SEM, PLS) and support managers in implementing more effective collaborative practices. It concludes that understanding the relationship between collaboration and integration is essential to strengthening the resilience and competitiveness of supply chains, especially in a scenario marked by digital transformations, sustainability, and complex global dynamics.DOI: https://doi.org/10.56238/sevened2025.036-001